Nano-Antibacterials Using Medicinal Plant Components: An Overview - Ghosh, Sourav; Nandi, Susmita; Basu, Tarakdas (Frontiers in Microbiology, 2022)
Abstract Gradual emergence of new bacterial strains, resistant to one or more antibiotics, necessitates development of new antibacterials to prevent us from newly evolved disease-causing, drug-resistant, pathogenic bacteria. Different inorganic and organic compounds have been synthesized as antibacterials, but with the problem of toxicity. Other alternative of using green products i.e., the medicinal plant extracts with biocompatible and potent antibacterial characteristics had also limitation because of their low aqueous solubility and thereby less bioavailability. Use of nanotechnological strategy appears to be a savior, where phytochemicals are nanonized through encapsulation or entrapment within inorganic or organic hydrophilic capping agents. Nanonization of such products not only makes them water soluble, but also helps to attain high surface to volume ratio and thereby high reaction area of the nanonized products with better therapeutic potential, over that of the equivalent amount of raw bulk products. In one hand, medicinal plant extracts, whose prime components are flavonoids, alkaloids, essential oils, etc., are nanonized (capped and stabilized) by polymers, lipids or clay materials for developing nanodrugs; on other hand, high antioxidant activity of those plant extracts are also used to reduce various metal salts to produce metallic nanoparticles. In this review, five medicinal plants viz., tulsi, turmeric, aloe vera, oregano and eucalyptus with promising antibacterial potential and the nanoformulations associated with the plants’ crude extracts and their respective major components (eugenol, curcumin, anthraquinone, carvacrol, eucalyptus oil) have been discussed with respect to their antibacterial potency.